Pornography Debate, Gaze and Spectatorship in Sarah Daniels’s Masterpieces - Lorek-Jezińska, Edyta (Text Matters: A Journal of Literature, Theory and Culture, 2013)
Masterpieces by Sarah Daniels has been described as a voice in the debate on pornography, expressing the anti-pornography position as opposed to the liberal feminist stance in this debate. Despite its ideological clarity reported by many reviewers and critics, the play has been commented upon as deficient or inadequate because of evoking conflicting interpretations and ambiguity. The paper argues that these deficiencies stem from the play’s concern with the distribution of agency and passivity along gender lines as well as the influence of generic and essentialist notions of genders on the perception of social and individual power relations particularly in the domain of eroticism and sexuality. One of the key issues of the play is the question to what extent and in what ways human perception is conditioned by the place of the subject in relation to the agency/passivity dichotomy and his or her viewing/reading position in relation to erotic and pornographic material.